Imaging and controlling plasmonic interference fields at buried interfaces - Tom T. A. Lummen (Nature Portfolio, 2016)
Visualizing surface plasmon polaritons at buried interfaces has remained elusive. Here, the authors develop a methodology to study the spatiotemporal evolution of buried near-fields within complex heterostructures, enabling the characterization of the next generation of plasmonic devices.